Balanced scorecard em serviços de saúde público e privado - Blanco, Luana Silva (2021)
The health sector is gaining more and more space in the market. The offer of health services, of different specialties, has been increasing exponentially in the last decades. Today, owners and service providers are beginning to understand that health services are also an enterprise. However, professionals in the field have little knowledge of management and many do not know how to use this knowledge in favor of their establishment. The lack of adequate management in health services can lead to not only financial losses, but the delivery of low quality services can have serious consequences for the health of the client / patient. In this sense, implementing a management system that is efficient and adapts to the demands of this type of service is essential for the sustainability of the health institution. The aim of the present study was to evaluate what the literature has found about the implementation of the Balanced Scorecard method in public and private health institutions. For that, the terms health service, health management and balanced scorecard were searched in the main databases, in Portuguese and English. 475 articles were found and after filtering according to the established inclusion and exclusion criteria, ten original articles were included and analyzed in this review. The analysis of the results showed that the balanced scorecard is simple and effective method of application for the public and private health sector.